(untitled) (Nigerian Journal of Technology, 2004)
In this paper, the flexibility of programmed control logic is exploited in the close loop control of a PWM thyristor voltage fed inverter supplying an induction heating tank load. The microprocessor used in the control is the MC6809 to which is interfaced the SY6522 versatile interface adapter (VIA). The microprocessor-based scheme performs the dual function of generating the thyristor gating signals as well as estimating and applying control actions to maintain the load power factor at unity and the power delivered to the load at a desired set-point value. The schemed also provides power circuit over-current and over-voltage protection against adverse changes in the inverter input supply and the load. The estimation of the control variables of the control scheme proportional plus integral controllers constitute the main control program while the application of thyristor gating signals and closed loop control actions are carried out in response to interrupts external to the microprocessor unit. Illustrative steady state and transient circuit of an experimental model of the induction heater are given.